Dichloromethane-free process for making cellulose triacetate fibers
By dissolving cellulose triacetate using solvents such as dimethylacetamide without dichloromethane, and performing jet tensile extension within a specific temperature range, the problem of insufficient CTA fiber filament factor in the prior art is solved. , realizes efficient and low-cost CTA fiber production.
Patent Information
- Application Number
- CN202380044338.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-03
- Filing Date
- 2023-06-01
- Publication Date
- 2025-02-18
AI Technical Summary
In the prior art, when manufacturing cellulose triacetate (CTA) fibers, it is difficult to achieve the goal of wire factor greater than or equal to 8.0 without using dichloromethane, and at the same time face the problems of high energy consumption and high operating costs.
Using a wet spinning method without dichloromethane, by dissolving cellulose triacetate in solvents such as dimethylacetamide, a spinning liquid is formed, and spraying and stretching is performed within a temperature range of 20°C to 40°C. Extend to form CTA fibers with a filament factor greater than or equal to 8.0.
It is achieved without using dichloromethane to produce CTA fibers with a wire factor greater than or equal to 8.0, reducing production costs and improving the mechanical properties of the fibers.
Smart Images

Figure CN119487244A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a methylene chloride-free wet spinning process for producing triacetate cellulose fibers having a silk factor of at least 8.0. Background Art
[0002] Cellulose triacetate (CTA) fibers have unique properties that make them well suited for textile applications. CTA has a certain degree of crystallinity and low modulus, giving it a silky feel and better "wash and wear" properties (i.e., better wrinkle retention and lower moisture absorption) than other cellulose-based polymers such as diacetate or viscose. Unfortunately, the crystallinity and polar nature of cellulose triacetate makes it insoluble in all but the strongest solvents.
[0003] Historically, dichloromethane (DCM) (also known as methylene chloride) and mixtures of DCM with alcohols (such as methanol and / or ethanol) have been used as the primary solvent systems for dissolving CTA with the goal of producing CTA fibers with acceptable tensile strength and elongation. However, environmental, health, and regulatory issues have greatly limited the use of DCM-based solvent systems. Other solvents have been evaluated as alternatives to DCM, but such evaluations have generally resulted in the production of CTA fibers with insufficient tensile strength, elongation at break, or fiber factor. Many DCM-free processes for producing CTA fibers require low-temperature coagulation baths that require cooling and / or insulation and high-temperature washing steps to remove residual solvent. Due to the energy required to cool and / or heat such process steps, these processes are more expensive to operate and are difficult (or even impossible) to retrofit into existing processes.
[0004] The manufacturing process of knitting and weaving yarns into textiles involves equipment and processing steps that subject the yarns to stresses and strains, which can cause fiber or yarn weakness and yarn breakage. Breakage can lead to process downtime, production loss, and reduced product quality. Tensile strength and elongation at break (percent elongation) are two properties of yarns that help determine whether a yarn is suitable for use in a given weaving method or on a given piece of equipment.
[0005] Tenacity is a measure of the force required to break a fiber or yarn at a given denier or decitex, and is typically expressed in units of g / den, g / dtex, or N / dtex. One technique for increasing the tenacity of CTA fibers and yarns is to utilize CTA polymers with a higher degree of polymerization (DP), as CTA polymers with higher DPs generally produce CTA fibers with higher tenacity. A common problem with this approach is that CTA polymers with higher DPs tend to produce more viscous CTA dopes that are difficult to filter and spin, especially at high speeds or in large volumes. The problem of high viscosity dopes is particularly acute when solvent systems that do not contain methylene chloride are used. Another means of increasing the tenacity of CTA fibers or yarns without using CTA polymers with higher DPs involves stretching or extending the coagulated fibers. Stretching / stressing the fibers can impart a degree of orientation to the fibers, thereby increasing tenacity. The problem with increasing tenacity by stretching is that the resulting increase in orientation reduces the ductility of the fiber, resulting in reduced elongation.
[0006] Elongation, also called elongation at break, is the ratio of the increase in length of a yarn or fiber sample when it breaks under a tensile load to the length of the sample before the load was applied. Elongation is expressed as a percentage and indicates how much the yarn or fiber can stretch before breaking. As mentioned above, stretching the coagulated CTA fibers to increase toughness will also reduce the elongation.
[0007] The Silk Factor (SF) is an empirically determined relationship between tenacity and elongation that is used to predict the failure envelope of a given fiber. Sf can be used to characterize the suitability of a fiber or yarn for a given process. The Silk Factor is calculated as Where tenacity is in g / den and elongation is expressed as a percentage. CTA fibers produced by DCM solvent system processes can exhibit silk factor values in the range of 9-11, minimum tenacity in the range of 1.8-2.0 g / den and elongation in the range of 20-30%. CTA yarns produced by processes without DCM solvent systems typically exhibit silk factor values in the range of 6-7 and are considered too weak to be used in many textile processes.
[0008] There is a need in the market to increase the silk factor of cellulose triacetate fibers produced using a methylene chloride-free process so that the resulting CTA fibers can be processed into filament yarns or converted into staple fibers for ring spinning and / or nonwoven applications.
[0009] It would be beneficial to provide products with such properties from a process that does not utilize a dichloromethane solvent system, which can cause operator health issues and environmental pollution issues. It would also be beneficial to operate such a DCM-free process at or near ambient temperature in critical process steps such as solidification. Summary of the invention
[0010] In one or more aspects, the present invention relates to a method for producing triacetate cellulose fiber having a silk factor greater than or equal to 8.0, the method comprising:
[0011] a) a dissolving step, wherein cellulose triacetate is dissolved in one or more spinning solution solvents not containing methylene chloride, the solvent comprising at least dimethylacetamide, to prepare a cellulose triacetate spinning solution;
[0012] b) a wet spinning step, wherein a triacetyl cellulose spinning solution is wet spun in a coagulation bath free of methylene chloride at a jet draw extension ratio in the range of 0.3 to 1.4 to form one or more triacetyl cellulose fibers, wherein the coagulation bath free of methylene chloride comprises dimethylacetamide and water, and wherein the coagulation bath free of methylene chloride is maintained at a temperature in the range of 20° C. to 40° C.;
[0013] c) and a drying step, wherein the one or more triacetyl cellulose fibers are dried in a manner that allows the one or more triacetyl cellulose fibers to shrink.
[0014] In one or more aspects, the present invention relates to wet-spun triacetate cellulose fibers. Typically, the cellulose ester fibers exhibit a silk factor of at least 8.0. In addition, the cellulose ester fibers comprise a DS 乙酰基 A cellulose ester having a number average degree of polymerization of at least 2.6 and not more than 200.
[0015] In one or more aspects, the present technology relates to cellulose triacetate spinning solutions. Typically, the CTA spinning solution comprises CTA in one or more solvents, the solvent comprising dimethylacetamide, dimethylformamide, or a combination thereof. In addition, the DS of the CTA 乙酰基 is at least 2.6 and the number average degree of polymerization is not more than 200. In addition, the CTA spinning solution exhibits a viscosity of not more than 1,000 poise when measured at 90°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Embodiments of the present invention are described herein with reference to the following drawings, in which:
[0017] Figure 1 An exemplary wet spinning system according to one embodiment of the present application is depicted; and
[0018] Figure 2A block diagram representing one possible arrangement of the steps of the claimed method is depicted.
[0019] Figure 3 The optimum coagulation bath concentration is plotted.
[0020] Figure 4 The effect of drying on dpf is plotted.
[0021] Figure 5 The effect of drying conditions on elongation is plotted.
[0022] Figure 6 The effect of drying conditions on toughness is plotted.
[0023] Figure 7 The effect of drying conditions on the silk factor is plotted.
[0024] Figure 8 The effect of the jet drawing extension ratio on the silk factor is plotted. DETAILED DESCRIPTION
[0025] The present application generally relates to a DCM-free wet spinning method for preparing triacetylcellulose fibers. Such fibers can be used for downstream fiber conversion and textile applications. In addition, this DCM-free CTA fiber can be produced by a wet spinning method. In this method, CTA is dissolved in a DCM-free solvent comprising dimethylacetamide and optionally one or more non-DCM solvents (e.g., dimethylformamide) to form a CTA spinning solution. The resulting CTA spinning solution is directly wet-spun into a DCM-free coagulation bath comprising dimethylacetamide and water through a plurality of small holes on the immersion surface of the spinneret. The DCM-free coagulation bath solvent concentration and conditions can be optimized to affect solidification and fiber formation. The coagulation bath temperature is preferably maintained at or near ambient temperature. In addition, under specific jet stretching extension conditions (e.g., the ratio of the fiber take-up speed to the calculated speed when the CTA spinning solution leaves the spinneret and enters the first coagulation bath), one or more CTA fibers are extended in a DCM-free coagulation bath to impart the desired polymer orientation therein when one or more CTA fibers are formed. The jet draw stretch ratio (JDSR) is calculated according to the following formula: Among them, v 1 is the velocity of the fiber leaving the spinneret surface (m / min), v 2 is the speed of the fiber at the take-up roller (m / min). 1 Calculated according to the following formula: where F 纺丝液 is the volume of spinning solution flowing to the spinneret, the number of holes is the number of holes on the spinneret surface, and A ihis the area of a single pore. In addition, the one or more CTA fibers may be further extended after the first coagulation bath to provide additional polymer orientation in the post-spray draw extension step.
[0026] More specifically, the wet spinning process described herein produces CTA fibers having a silk factor greater than or equal to 8.0 via wet spinning without the use of DCM-based solvents. As the fibers are formed from the spinneret, filtering the CTA spinning solution can improve processability. The CTA that can be utilized in the present invention can have a lower degree of polymerization ("DP") than the higher DP CTA that is traditionally utilized in wet spinning processes without dichloromethane. The lower DP CTA can allow the use of a higher solid spinning solution, which in turn can increase the yield of the wet spinning process and can allow for better morphological properties during fiber formation in the first coagulation bath.
[0027] Figure 1 An exemplary wet spinning system for producing CTA fibers is depicted. Figure 1 The illustration is a non-limiting example, in which certain features may be omitted and / or rearranged. Figure 2 The additional features described in can also be added to Figure 1 In the system shown in FIG.
[0028] Figure 1 The wet spinning system described herein can produce one or more CTA fibers exhibiting a silk factor greater than or equal to 8.0. Various characteristics and properties of the wet spinning process and the resulting CTA fibers are described below. It should be noted that while all of the following characteristics and properties may be listed individually, it is contemplated that each of the following characteristics and / or properties of the wet spinning process, CTA spinning solution, and CTA fibers are not mutually exclusive and may be combined and present in any combination.
[0029] Go to Figure 1 , in the dissolving step, at least one cellulose ester and at least one dissolving solvent may be introduced into a spinning solution mixer 10 to form a CTA spinning solution. The spinning solution mixer 10 may include any conventional device capable of mixing CTA and a dissolving solvent. An exemplary spinning solution mixer 10 may include a continuous stirred tank reactor ("CSTR"). While in the spinning solution mixer 10, the CTA and the dissolving solvent may be subjected to temperature and mixing conditions that are conducive to the dissolution of the CTA into the dissolving solvent, thereby forming a CTA spinning solution. For example, it is known in the art that some cellulose ester spinning solutions can be prepared by first cooling the spinning solution to a lower temperature to allow the solvent to better mix with the polymer, and then heating it to the final mixing temperature. In addition, some spinning solution preparation methods prefer faster "flash" type heating to quickly make the system a solution while minimizing degradation.
[0030] In one embodiment or in combination with any of the other mentioned embodiments, the CTA spinning dope may comprise a solids content of at least 15 wt%, at least 16 wt%, at least 17 wt%, at least 18 wt%, at least 19 wt%, at least 20 wt%, at least 21 wt%, at least 22 wt%, or at least 23 wt%, and / or no more than 35 wt%, no more than 34 wt%, no more than 33 wt%, no more than 32 wt%, no more than 31 wt%, no more than 30 wt%, no more than 29 wt%, no more than 28 wt%, no more than 27 wt%, no more than 26 wt%, or no more than 25 wt%, based on the total weight of the spinning dope.
[0031] The CTA introduced into the spinning solution mixer 10 may comprise any cellulose triacetate known in the art. The cellulose triacetate useful in the present invention generally comprises repeating units of the following structure:
[0032]
[0033] Where R 1 , R 2 and R 3 It is an acetyl functional group.
[0034] For cellulose ester polymers, the level of substitution is often expressed in terms of the degree of substitution ("DS"), which is the average number of non-OH substituents per anhydroglucose unit ("AGU"). In general, conventional cellulose contains three hydroxyl groups per AGU unit that can be substituted; therefore, the value of DS can range from zero to three. However, due to the presence of end groups, the total degree of substitution for low molecular weight CTAs can be slightly higher than 3. Since DS is a statistical average, a value of 1 does not guarantee that there is one substituent for each AGU. In some cases, there may be unsubstituted AGUs, some with two substituents and some with three substituents, and typically the value is a non-integer. "Total DS" is defined as the average number of all substituents per AGU. The degree of substitution per AGU can also refer to a specific substituent, such as, for example, hydroxyl, acetyl, propionyl, or butyryl.
[0035] In one embodiment or in combination with any of the other mentioned embodiments, the CTA comprises a DS of at least 2.60, at least 2.65, at least 2.70, at least 2.75, at least 2.80, at least 2.82, or at least 2.85, and / or no more than 3.00, no more than 2.99, no more than 2.95, no more than 2.9, or no more than 2.88. 乙酰基 In certain embodiments, the CTA may comprise a DS ranging from 2.60 to 3.00, 2.65 to 2.99, 2.70 to 2.95, 2.75 to 2.90, 2.80 to 2.88, 2.82 to 2.88, or 2.85 to 2.88.乙酰基 .
[0036] Additionally or alternatively, in one embodiment or in combination with any of the other mentioned embodiments, the CTA comprises a DS of at least 0.0, at least 0.01, at least 0.05, at least 0.10 or at least 0.12, and / or no more than 0.4, no more than 0.35, no more than 0.30, no more than 0.25, no more than 0.20, no more than 0.18 or no more than 0.15. OH In certain embodiments, the cellulose ester comprises DSOH in the range of 0.0 to 0.4, 0.01 to 0.35, 0.05 to 0.30, 0.10 to 0.25, 0.12 to 0.18, or 0.12 to 0.15.
[0037] In one embodiment or in combination with any of the other mentioned embodiments, the CTA may have a degree of acetylation of at least 56.2%, at least 56.9%, or at least 57.6%, and / or no more than 61.5%, no more than 61.0%, no more than 60.3%, no more than 59.7%, or no more than 59%. In certain embodiments, the CTA may have a degree of acetylation ranging from 56.2% to 61.5%, from 56.9% to 61%, from 57.6% to 60.3%.
[0038] Additionally or alternatively, in one embodiment or in combination with any of the other mentioned embodiments, the CTA may have a hydroxyl content of at least 0 wt%, at least 0.3 wt%, at least 0.6 wt%, at least 0.9 wt%, or at least 1.2 wt%, and / or no more than 2.4 wt%, no more than 2.1 wt%, no more than 1.8 wt%, or no more than 1.5 wt%. In certain embodiments, the CTA may have a hydroxyl content in the range of 0.0 to 2.4, 0.3 to 2.1, 0.6 to 1.8, or 0.9 to 1.5 wt%.
[0039] In one embodiment or in combination with any of the other mentioned embodiments, the CTA may have a number average degree of polymerization of at least 90, at least 100, at least 110, at least 120, at least 130, at least 140, at least 150, or greater than 150, or at least 151, or at least 153, or at least 155, or at least 160, at least 170, at least 180, at least 190, or at least 200. Additionally or alternatively, in one embodiment or in combination with any of the other mentioned embodiments, the CTA may have a value of not more than 300, or not more than 290, or not more than 280, or not more than 270, or not more than 260, or not more than 250, or not more than 240, or not more than 230, or not more than 220, or not more than 210, or not more than 200, or not more than 190, or not more than 180, or not more than 170, or not more than 160, or not more than 150, or not more than 149, or not more than 148, or not more than 147, or not more than 146, or not more than 145, or not more than 144. , or not more than 143, or not more than 142, not more than or higher than 141, not more than 140, not more than 139, not more than 138, not more than 137, not more than 136, not more than 135, not more than 134, not more than 133, not more than 132, not more than 131, not more than 130, not more than 129, not more than 128, not more than 127, not more than 126, not more than 125, not more than 124, not more than 123, not more than 122, not more than 121, not more than 120, not more than 119, not more than 118, not more than 117, not more than 116 or not more than 115 number average degree of polymerization. In certain embodiments, the CTA may have a number average degree of polymerization in the range of 90 to 300, or 90 to 250, or 90 to 250, or 90 to 270, or 90 to 250, or 90 to 230, or 90 to 210, or 90 to 200, 90 to 190, 90 to 180, 90 to 170, 90 to 160, 90 to 150, 100 to 200, 100 to 190, 100 to 180, 100 to 170, 100 to 160, 100 to 150, or 90 to less than 150, or 90 to 149, or 90 to 147, or 90 to 145.
[0040] In one embodiment or in combination with any of the other mentioned embodiments, the CTA may have a number average absolute molecular weight of at least 10,000, at least 15,000, at least 20,000, or at least 25,000, and / or no more than 75,000, no more than 70,000, no more than 65,000, no more than 60,000, no more than 55,000, no more than 50,000, no more than 45,000, no more than 40,000, no more than 35,000, or no more than 30,000, as measured by absolute molecular weight via gel permeation chromatography ("GPC"). In certain embodiments, the CTA may include a number average absolute molecular weight in the range of 10,000 to 75,000, 10,000 to 65,000, or 15,000 to 35,000, as measured by absolute molecular weight via GPC.
[0041] In one embodiment or in combination with any of the other mentioned embodiments, the CTA may comprise a weight average absolute molecular weight of at least 50,000, at least 55,000, at least 60,000, at least 65,000, at least 70,000, at least 75,000, at least 80,000, or at least 85,000, and / or no more than 150,000, no more than 140,000, no more than 130,000, no more than 120,000, no more than 110,000, no more than 100,000, or no more than 95,000, as measured by absolute molecular weight via GPC. In certain embodiments, the CTA may comprise a weight average absolute molecular weight in the range of 50,000 to 150,000, 70,000 to 120,000, or 80,000 to 95,000, as measured by absolute molecular weight via GPC.
[0042] In one embodiment or in combination with any of the noted embodiments, the CTA can have any of the above-mentioned weight average absolute molecular weights, as measured according to ASTM D6474.
[0043] In one embodiment or in combination with any of the other mentioned embodiments, the CTA may comprise at least 1%, at least 2%, at least 5%, at least 10%, at least 15%, at least 20%, at least 25% crystallinity as measured according to ASTM F2625. Additionally or alternatively, in one embodiment or in combination with any of the other mentioned embodiments, the CTA may have a crystallinity of no more than 25%, no more than 20%, no more than 15%, no more than 10%, no more than 9%, no more than 8%, no more than 7%, no more than 6%, no more than 5%, no more than 4%, no more than 3%, no more than 2%, or no more than 1%, as measured according to ASTM F2625. In certain embodiments, the CTA may comprise 1% to 25% crystallinity as measured according to ASTM F2625.
[0044] In one embodiment or in combination with any of the other mentioned embodiments, the CTA may exhibit a glass transition temperature (“Tg”) of at least 120°C, at least 125°C, at least 130°C, at least 135°C, at least 140°C, at least 145°C, at least 150°C, at least 155°C, at least 160°C, at least 165°C, at least 170°C, at least 175°C, at least 180°C, or at least 185°C, and / or no more than 250°C, no more than 245°C, no more than 240°C, no more than 235°C, no more than 230°C, no more than 225°C, no more than 220°C, no more than 215°C, no more than 210°C, no more than 205°C, no more than 200°C, no more than 195°C, no more than 190°C, or no more than 185°C. g ”). In order to determine the T of CTA g , the samples were dried to a moisture level below 10 wt %.
[0045] CTA can be produced by any method known in the art. Examples of methods for producing cellulose esters are taught in Kirk-Othmer, Encyclopedia of Chemical Technology, 5th Edition, Volume 5, Wiley-Interscience, New York (2004), pages 394-444.
[0046] One method of producing cellulose triacetate involves esterification of cellulose by mixing cellulose with an appropriate organic acid, anhydride, and catalyst. The cellulose is then converted to a cellulose triester, which can then be filtered to remove any gel particles or fibers. Water is then added to the mixture to precipitate the CTA. The CTA can then be washed with water to remove reaction byproducts, followed by dehydration and drying.
[0047] Cellulose is the starting material for the production of CTA and is available in different grades and sources, such as from cotton linters, softwood pulp, hardwood pulp, corn fiber and other agricultural sources, and bacterial cellulose, etc. The starting material used to produce CTA may affect the resulting hemicellulose content in the resulting CTA.
[0048] In one embodiment or in combination with any of the other mentioned embodiments, the CTA may comprise a hemicellulose content of at least 0.5 wt%, at least 1 wt%, at least 2 wt%, at least 3 wt%, at least 4 wt%, at least 5 wt%, at least 6, or at least 7 wt%. Additionally or alternatively, in one embodiment or in combination with any of the other mentioned embodiments, the CTA may comprise a hemicellulose content of no more than 10 wt%, no more than 9 wt%, no more than 8 wt%, no more than 7 wt%, no more than 6 wt%, no more than 5 wt%, no more than 4 wt%, no more than 3 wt%, no more than 2 wt%, or no more than 1 wt%.
[0049] The dissolving solvent added to the spinning solution mixer 10 may include one or more solvents capable of dissolving cellulose esters, particularly cellulose triacetate. A sufficient amount of the dissolving solvent should be added to effectively dissolve the CTA, thereby forming a CTA spinning solution. In one embodiment or in combination with any of the other mentioned embodiments, the CTA spinning solution may contain at least 25 wt%, at least 50 wt%, at least 55 wt%, at least 60 wt%, at least 65 wt%, at least 70 wt%, at least 75 wt%, at least 80 wt%, at least 85 wt%, at least 90 wt%, at least 95 wt%, or at least 99 wt% of one or more dissolving solvents, based on the total weight of the spinning solution.
[0050] In one embodiment or in combination with any of the other mentioned embodiments, the dissolving solvent may contain at least one alkylamide compound. An amide is a functional group in which a carbonyl carbon atom is connected to a nitrogen atom and a hydrogen atom or a carbon atom via a single bond. An amide is an organic compound having the general formula RC(=O)NR'R". Alkylamides replace at least one of the R, R' and R" groups with a hydrogen or alkyl group.
[0051] In some further embodiments, the dissolving solvent may comprise dimethylacetamide, dimethylformamide, formamide, N-formylmorpholine, N-methyl-2-pyrrolidone, N-methylformamide, 2-pyrrolidone, tetramethylurea, N-vinylacetamide or N-vinylpyrrolidone, or a combination thereof. In certain embodiments, the dissolving solvent may comprise dimethylacetamide, dimethylformamide or a combination thereof.
[0052] In one embodiment or in combination with any of the other mentioned embodiments, the CTA dope is free of DCM and may contain trace amounts of, or be substantially free of, dichloromethane, acetone, ionic liquids, N-methylmorpholine N-oxide (NMMO), tertiary amine oxides, metal oxide precursors, acetic acid, diols, or combinations thereof. In certain embodiments, the CTA dope may contain less than 10 wt%, less than 9 wt%, less than 8 wt%, less than 7 wt%, less than 6 wt%, less than 5 wt%, less than 4 wt%, less than 3 wt%, less than 2 wt%, less than 1 wt%, less than 0.5 wt%, less than 0.1 wt%, less than 0.05 wt%, or less than 0.01 wt% of dichloromethane, acetone, ionic liquids, N-methylmorpholine N-oxide (NMMO), tertiary amine oxides, metal oxide precursors, acetic acid, diols, or combinations thereof, based on the total weight of the CTA dope.
[0053] Due to the type of cellulose ester and dissolving solvent used, the CTA spinning solution can exhibit an ideal operating viscosity. In one embodiment or in combination with any of the other mentioned embodiments, the CTA spinning solution can exhibit a viscosity of at least 10, at least 20, at least 30, at least 40, at least 50, at least 60, at least 70, at least 80, at least 90, or at least 100, and / or no more than 5,000, no more than 4,000, no more than 3,000, no more than 2,000, no more than 1,500, no more than 1,000, no more than 950, no more than 900, no more than 850, no more than 800, no more than 750, no more than 700, no more than 650, no more than 600, no more than 550, or no more than 500 poise at the spinning temperature utilized. Alternatively, the viscosity of the spinning solution can have any of these values when a sample of the spinning solution composition for spinning is taken and measured at 100° C. or 110° C. It should be noted that this "when measured" standard does not require that CTA spinning solutions be utilized only at specified temperatures; rather, this temperature standard merely provides a temperature threshold for measuring the viscosity of CTA spinning solutions. Therefore, the "when measured" threshold does not in any way reflect the use or practice of actual CTA spinning solutions. The viscosity defined here is the "zero" shear viscosity obtained by extrapolating to very low shear rates when the viscosity is plotted against the shear rate, or by using a Brookfield viscometer with a low spindle RPM. Ideally, the CTA spinning solution has a viscosity of no more than 1,000, or no more than 950, no more than 900, no more than 850, no more than 800, no more than 750, no more than 700, no more than 650, no more than 600, no more than 550, or no more than 500 poise at the spinning temperature utilized or when measured at 100°C or at 110°C.
[0054] In one embodiment or in combination with any of the other mentioned embodiments, the CTA spinning solution may contain some additives in addition to the CTA or may not contain any additives. Such additives may include, but are not limited to, plasticizers, antioxidants, heat stabilizers, pro-oxidants, acid scavengers, inorganic substances, pigments, colorants, matting agents, or combinations thereof.
[0055] Back to Figure 1 After the CTA spinning solution is formed in the spinning solution mixer 10, the newly formed CTA spinning solution can be sent to an optional spinning solution storage tank 20 for temporary storage and / or degassing. The spinning solution storage tank 20 may include any conventional storage tank known in the art that is capable of storing CTA spinning solution. When stored in the storage tank 20, the CTA spinning solution can be subjected to conditions that are conducive to maintaining the physical properties of the spinning solution and / or removing bubbles introduced during the mixing step. For example, storing the spinning solution at low temperature for too long will result in unacceptable gelation, which will have an adverse effect on spinnability. This is especially true when the solid level of the spinning solution is increased to a higher level. Therefore, the temperature and pressure of the storage tank and / or the degassing tank 20 can be optimized as needed to enhance and maintain the quality of the CTA spinning solution.
[0056] Next, if Figure 1 As shown, the CTA dope can be pumped from the dope storage tank 20 via pump 30 to a filter 40 which can remove any large and unwanted particles and gels from the CTA dope prior to spinning. The filter can include any conventional filter device and filter type known in the art.
[0057] After the dissolving step, in the wet spinning step, the filtered CTA dope can be pumped to a spinneret 51, which is positioned to immerse at least the spinneret face in a coagulation bath 50 without DCM. In one embodiment or in combination with any other mentioned embodiments, the temperature of the filtered CTA dope can be maintained at least 20° C., at least 25° C., at least 30° C., at least 35° C., at least 40° C., at least 45° C., at least 50° C., at least 55° C., at least 60° C., at least 65° C., at least 70° C., at least 75° C., or at least 80° C., and / or no more than 120° C., no more than 110° C., or no more than 100° C. In certain embodiments, the surface of the spinneret 51 can be maintained at a temperature in the range of 20 to 120° C., 20 to 100° C., 20 to 80° C., 20 to 60° C., or 20 to 40° C.
[0058] like Figure 1As shown, the filtered CTA spinning solution is metered through a spinneret 51 to form one or more (determined by the number of holes on the spinneret surface) CTA fibers 52, which are coagulated in a coagulation bath 50 that does not contain DCM. In addition, when coagulating in a coagulation bath 50 that does not contain DCM, the resulting one or more CTA fibers 52 are subjected to jet drawing extension. Figure 1 As shown, the method for forming CTA fibers 52 is a wet spinning method. The wet spinning method is a method of spinning one or more CTA fibers 52 by metering a spinning solution through a spinneret 51, the surface of which has one or more holes, wherein the spinneret surface is immersed in a coagulation bath 50 that does not contain DCM. The shape and size of the holes on the spinneret 51 help determine the size and cross-section of the one or more CTA fibers 52. The number of holes on the spinneret surface determines the number of fibers 52 that are formed simultaneously when the spinning solution is metered through the spinneret 51. When the spinning solution passes through the holes on the spinneret surface, it enters the liquid of the coagulation bath 50 that does not contain DCM in the form of one or more individual fibers.
[0059] More specifically, in various embodiments, the filtered CTA spinning solution can be spun at a rate of about 1 to 500 m / min through a spinneret hole having a hole area equivalent to a circular diameter of 20 to 200 microns. In one embodiment or in combination with any other mentioned embodiments, the spinneret 51 can be maintained at at least 20°C, at least 25°C, at least 30°C, at least 35°C, at least 40°C, at least 45°C, at least 50°C, at least 55°C, at least 60°C, at least 65°C, at least 70°C, at least 75°C, or at least 80°C, and / or at a temperature of no more than 200°C, no more than 180°C, no more than 160°C, no more than 140°C, no more than 120°C, no more than 110°C, or no more than 100°C. In certain embodiments, the surface of the spinneret 51 can be maintained at a temperature in the range of 20 to 200°C, 20 to 120°C, 20 to 80°C, 20 to 60°C, or 20 to 40°C.
[0060] In one embodiment or in combination with any of the other mentioned embodiments, based on the low DP and / or low molecular weight of the CTA forming the CTA dope, the CTA dope may exhibit a viscosity of at least 10, at least 20, at least 30, at least 40, at least 50, at least 60, at least 70, at least 80, at least 90, or at least 100, and / or no more than 5,000, no more than 4,000, no more than 3,000, no more than 2,000, no more than 1,500, no more than 1,000, no more than 950, no more than 900, no more than 850, no more than 800, no more than 750, no more than 700, no more than 650, no more than 600, no more than 550, or no more than 500 poise at the spinning temperature prior to or as it is fed into the spinneret 51. This spinning temperature is nominally the temperature of the dope as it passes through and enters the spinneret. As noted above, the viscosity defined herein is the "zero" shear viscosity obtained by extrapolation to very low shear rates when the viscosity is plotted against shear rate, or by using a Brookfield viscometer with a low spindle RPM.
[0061] At the spinneret 51, the filtered CTA spinning solution can be extruded through one or more holes to form one or more CTA fibers 52. At the spinneret 51 and in the coagulation bath 50 without DCM, the one or more CTA fibers 52 can be gathered together to form bundles, ribbons or yarns of hundreds or even thousands of individual fibers 52 in the coagulation bath 50 without DCM. These bundles or ribbons or yarns can include at least 1, at least 10, at least 50, at least 100, at least 150, at least 200, at least 250, at least 300, at least 350 or at least 400, and / or no more than 10,000, no more than 5,000, no more than 1,000, no more than 900, no more than 800, no more than 700 or no more than 600 fibers. The spinneret 51 can be operated at any suitable speed to produce one or more CTA fibers 52, which are then assembled into bundles or ribbons or yarns of desired size and shape. As used herein, the term "single filament fiber" refers to the continuous fiber initially produced by the spinneret 51.
[0062] In one embodiment or in combination with any of the other mentioned embodiments, the one or more CTA fibers 52 are jet-drawn stretched in a coagulation bath 50 that does not contain DCM at a jet-draw stretch ratio (JDSR) of 0.3 to 1.4 (inclusive). More specifically, in one embodiment or in combination with any of the other mentioned embodiments, the one or more CTA fibers 52 can be stretched with a JDSR of at least 0.3, and / or no more than 1.4, or no more than 1.3, or no more than 1.2, or no more than 1.1, or no more than 1.0, or no more than 0.9, or no more than 0.8, or no more than 0.7, or no more than 0.6, or no more than 0.5, or no more than 0.4. Additionally or alternatively, the JDSR can be at least 0.3, or at least 0.4, or at least 0.5, or at least 0.6, or at least 0.7, or at least 0.8. For example, one or more CTA fibers may extend at a JDSR in the range of 0.3 to 1.4, or 0.3 to 1.3, or 0.3 to 1.2, or 0.3 to 1.1, or 0.3 to 1.0, or 0.3 to 0.9, or 0.3 to 0.8, or 0.3 to 0.7, or 0.3 to 0.6, or 0.3 to 0.5, or 0.3 to 0.4.
[0063] JDSR is the surface velocity (v2) of the first driven take-up roll 53 as the one or more CTA fibers are pulled or drawn through the coagulation bath 50 without DCM divided by the velocity (v 1 ). JDSR is 0.3 A JDSR of 1.0 means that the fiber is drawn from the coagulation bath 50 without DCM at a rate slower than the rate at which the one or more CTA fibers leave the spinneret surface, thereby causing the one or more CTA fibers to coagulate in a relaxed state. A JDSR of 1.0 means that the one or more CTA fibers are drawn from the coagulation bath at the same rate as they leave the spinneret surface. A JDSR of 1.2 means that the one or more CTA fibers are drawn from the coagulation bath 20% faster than the rate at which the one or more CTA fibers leave the spinneret surface, thereby causing the one or more CTA fibers to extend as they coagulate. The velocity (v) of the CTA spinning solution leaving the spinneret surface 1 ) is calculated by dividing the volume flow rate of filtered CTA spinning solution metered into the spinneret per minute by the number of holes in the spinneret face and then dividing the per hole volume flow value by the cross-sectional area of a single hole in the spinneret face to determine the velocity of the one or more CTA fibers leaving the spinneret face. The surface velocity (v) of the take-up roll 53 is 2 ) is the speed calculated by multiplying the circumference of the take-up roller 53 by the number of revolutions per minute of the roller.
[0064] As described above, the jet-draw stretching occurs in a coagulation bath 50 that does not contain DCM. Thus, in such embodiments, any stretching of the one or more CTA fibers after the first driven take-up roll 53 is not a jet-draw stretching stretch. The stretching that occurs after the first driven take-up roll 53 (regardless of whether the one or more CTA fibers are stretched submerged in liquid or in air) is a post-jet-draw stretching stretch. The post-jet-draw stretch ratio (PJDSR) of any post-jet-draw stretching process step is the ratio of the velocity (v) of the one or more fibers exiting the process step to the velocity (v) of the one or more fibers exiting the process step. out ) divided by the velocity (v) of the one or more CTA fibers entering said step in ). In such embodiments, the one or more CTA fibers may undergo no post-jet draw extension step, one post-jet draw extension step, or more than one post-jet draw extension step. Any extension of the one or more CTA fibers after the first driven take-up roll 53 is a separate operation from the jet draw extension that is performed in the coagulation bath 50 without DCM before the crystalline structure of the polymer fibers is fully formed.
[0065] The coagulation bath 50 without DCM contains any of the following:
[0066] Water and a spinning solution solvent, or water, a spinning solution solvent and a coagulation solvent other than the spinning solution solvent.
[0067] If a coagulation solvent is used, it can be an aqueous coagulation solvent containing water. Water is considered to be an antisolvent or coagulant. Based on the total weight of all liquids in the coagulation bath 50, the total amount of water from all sources contained in the coagulation bath 50 can be at least 1 weight %, at least 10 weight %, at least 15 weight %, at least 20 weight %, at least 25 weight %, at least 30 weight %, at least 35 weight %, at least 40 weight %, at least 45 weight %, at least 50 weight %, at least 55 weight %, at least 60 weight %, at least 65 weight %, at least 70 weight %, at least 75 weight %, at least 80 weight %, at least 85 weight %, at least 90 weight %, at least 95 weight % or at least 99 weight % of water. Additionally or alternatively, in one embodiment or in combination with any of the other mentioned embodiments, the amount of water in the coagulation bath 50 may be no more than 99 wt%, no more than 90 wt%, no more than 80 wt%, no more than 70 wt%, no more than 60 wt%, no more than 50 wt%, no more than 40 wt%, no more than 30 wt%, or no more than 20 wt% water, based on the total weight of the liquid in the coagulation bath 50. In certain embodiments, the coagulation bath 50 may contain 10 wt% to 99 wt%, 20 wt% to 80 wt%, 25 wt% to 70 wt%, or 30 wt% to 60 wt% water, based on the total weight of the liquid in the coagulation bath 50. The total amount of the spinning solution solvent in the coagulation bath 50 may be at least 0.1%, at least 0.5%, at least 1.0%, at least 2.0%, or at least 3.0%, based on the weight of all the liquid in the coagulation bath. Additionally or alternatively, the total amount of the spinning solution solvent in the coagulation bath 50 may be no more than 80%, no more than 75%, no more than 70%, no more than 65%, no more than 60%, no more than 55%, or no more than 50%, based on the weight of all liquids in the coagulation bath 50. Suitable ranges of the spinning solution solvent in the coagulation bath 50, based on the weight of all liquids in the coagulation bath 50, include 0.1 wt % to 80 wt %, or 0.5 wt % to 80 wt %, or 1 wt % to 80 wt %, or 0.1 wt % to 75 wt %, or 0.5 wt % to 75 wt %, or 1 wt % to 75 wt %, or 0.1 wt % to 70 wt %, or 0.5 wt % to 70 wt %, or 1 wt % to 70 wt %, or 0. 1 wt % to 65 wt %, or 0.5 wt % to 65 wt %, or 1 wt % to 65 wt %, or 0.1 wt % to 60 wt %, or 0.5 wt % to 60 wt %, or 1 wt % to 60 wt %, or 0.1 wt % to 55 wt %, or 0.5 wt % to 55 wt %, or 1 wt % to 55 wt %, or 0.1 wt % to 50 wt %, or 0.5 wt % to 50 wt %, or 1 wt % to 50 wt %.The spinning solution solvent in the coagulation bath 50 can be obtained by adding fresh spinning solution solvent to the coagulation bath, or by washing or seeping residual spinning solution solvent from the fiber when the fiber passes through the coagulation bath 50, or both. The spinning solution solvent can be at least one of the same solvents as the solvent used to dissolve the CTA polymer in the spinning solution composition before spinning. In one embodiment or in combination with any other mentioned embodiments, the coagulation bath 50 contains a spinning solution solvent obtained only from residual spinning solution solvent on or in the fiber. In one embodiment or in combination with any other mentioned embodiments, the spinning solution solvent in the coagulation bath 50 comes from both residual spinning solution solvent in or on the fiber and fresh supplemental spinning solution solvent added to the coagulation bath 50.
[0068] The total amount of coagulation solvent (excluding any amount of water, regardless of its source) in the coagulation bath 50 without DCM may be at least 1 wt %, at least 5 wt %, at least 10 wt %, at least 15 wt %, or at least 20 wt % of the additional solvent, based on the total weight of the liquid in the coagulation bath 50. Additionally or alternatively, in one embodiment or in combination with any other mentioned embodiments, the coagulation solvent may include no more than 90 wt %, no more than 80 wt %, no more than 70 wt %, no more than 65 wt %, no more than 60 wt %, no more than 50 wt %, no more than 40 wt %, no more than 30 wt %, no more than 20 wt %, no more than 10 wt %, no more than 5 wt %, or no more than 1 wt % of the additional solvent, based on the total weight of the liquid in the coagulation bath 50 without DCM. The amount of coagulation solvent in the DCM-free coagulation bath 50 may be in the range of 1 wt % to 90 wt %, 5 wt % to 80 wt %, 10 wt % to 70 wt %, 20 wt % to 65 wt %, 5 wt % to 65 wt %, or 10 wt % to 60 wt % of the at least one additional solvent, based on the total weight of the liquid in the DCM-coagulation bath 50.
[0069] Suitable solidification solvent comprises at least one alkylamide compound.The example of suitable alkylamide compound solvent comprises dimethylacetamide, dimethylformamide, formamide, N-formylmorpholine, N-methyl-2-pyrrolidone, N-methylformamide, 2-pyrrolidone, tetramethylurea, N-vinylacetamide or N-vinylpyrrolidone, or its combination.In one embodiment or with any other embodiment combination mentioned, solidification solvent comprises dimethylacetamide, dimethylformamide or its combination.
[0070] In one embodiment or in combination with any other mentioned embodiments, no DCM is added to the DCM-free coagulation bath 50, or the DCM-free coagulation bath 50 does not contain any DCM, or the DCM-free coagulation bath 50 contains only trace amounts (e.g., less than 1 wt%, or less than 5,000 ppm, or less than 1,000 ppm, or less than 500 ppm, or less than 100 ppm) of DCM. The DCM-free coagulation bath 50 may contain trace amounts of DCM due to insufficient washing and cleaning of the spinning solution tank in a previous run or the presence of DCM in the DCM-free coagulation bath 50, even if the added coagulation solvent does not contain any DCM.
[0071] In one embodiment or in combination with any other mentioned embodiments, DCM and one or more additional solvents are not added to the DCM-free coagulation bath 50, or the DCM-free coagulation bath does not contain any DCM or at least one or more additional solvents, or the DCM-free coagulation bath 50 contains only trace amounts (e.g., less than 1 wt%, or less than 5,000 ppm, or less than 1,000 ppm, or less than 500 ppm, or less than 100 ppm) of DCM and one or more additional solvents. These additional solvents include acetone, ionic liquids, N-methylmorpholine N-oxide (NMMO), tertiary amine oxides, metal oxide precursors, acetic acid, diols, or combinations thereof.
[0072] In one embodiment or in combination with any of the other mentioned embodiments, the DCM-free coagulation bath 50 may contain less than 10 wt%, less than 9 wt%, less than 8 wt%, less than 7 wt%, less than 6 wt%, less than 5 wt%, less than 4 wt%, less than 3 wt%, less than 2 wt%, less than 1 wt%, less than 0.5 wt%, less than 0.1 wt%, less than 0.05 wt% or less than 0.01 wt% of any of DCM, acetone, ionic liquids, N-methylmorpholine N-oxide (NMMO), tertiary amine oxides, metal oxide precursors, acetic acid, diols, based on the total weight of the liquid in the DCM-free coagulation bath 50, or the coagulation bath 50 contains less than the combined amount of all of these solvents.
[0073] Additionally or alternatively, in one embodiment or in combination with any of the other mentioned embodiments, the coagulation bath 50 (which includes the coagulation solvent) without DCM can be maintained at a temperature of at least 20° C., or at least 25° C., and / or no more than 40° C., no more than 35° C. In certain embodiments, the first coagulation bath 50 (which includes the coagulation solvent) can be maintained at a temperature in the range of 20 to 40° C., 20 to 35° C., 20 to 30° C., 25 to 40° C., 30 to 40° C., 35 to 40° C., or 25 to 35° C.
[0074] although Figure 1A specific wet spinning technique is depicted, but it is contemplated that the downstream process steps (after the take-up roll 53) may be arranged in a variety of alternative sequences. For example, the downstream process steps may include one or more additional coagulation steps, one or more washing steps, one or more post-spray stretching steps, one or more fiber finish application steps, one or more drying steps, one or more heat treatment steps, a crimping step, a cutting step, a winding step, a packaging step, or a combination thereof, which may be arranged in a different sequence.
[0075] Ideally, the one or more CTA fibers 52 formed in the DCM-free coagulation bath 50 are monocomponent fibers, meaning that they have a single continuous phase. Monocomponent fibers may contain only one material (e.g., CTA) or a uniformly blended combination. Monocomponent fibers are distinguished from, and are not considered to be, "bicomponent" or "multicomponent fibers," which are characterized by internal phases or boundaries that define regions of different compositions within the outer surface of the fiber. In one embodiment or in combination with any of the other mentioned embodiments, the fibers in or emerging from the first coagulation bath, or the final finished fibers, are monocomponent and contain at least 50 wt%, at least 55 wt%, at least 60 wt%, at least 65 wt%, at least 70 wt%, at least 75 wt%, at least 80 wt%, at least 85 wt%, at least 90 wt%, at least 95 wt%, at least 99 wt%, or at least 99.9 wt%, or 100 wt% of a single type of polymer, such as CTA, based on the total weight of the fibers and excluding the weight of any finish or cutting lubricant.
[0076] The one or more CTA fibers 52 discharged from the spinneret 51 can have any suitable cross-sectional shape. Exemplary cross-sectional shapes include, but are not limited to, circular, bean-shaped, ribbon-shaped, crenulated, multi-lobed, or non-circular (non-circular). It is well known in the art that the shape of the cross section is generally determined by the balance between the rate at which the coagulation in the coagulation bath diffuses into the fiber and the rate at which the solvent diffuses out of the fiber. When these are balanced, the fiber is closer to a circle. For example, adjusting the bath temperature and / or solvent level can make the fiber shape more or less circular, or bean-shaped or ribbon-shaped / sliver-shaped.
[0077] In one embodiment or in combination with any other mentioned embodiments, one or more fibers 52 discharged from the spinneret 51 can have a substantially circular cross-sectional shape. The term "cross-section" as used herein generally refers to the cross-section of a fiber measured perpendicular to the direction of fiber elongation. Quantitative image analysis ("QIA") can be used to determine and measure the cross-sectional area and perimeter of the fiber.
[0078] The cross-sectional shape of a single fiber can also be characterized according to its deviation from a circular cross-sectional shape. In some cases, this deviation can be characterized by the shape factor of the fiber, which is determined by the following formula:
[0079]
[0080] In some embodiments, the shape factor of one or more CTA fibers can be from 1 to 2, 1 to 1.8, 1 to 1.7, 1 to 1.5, 1 to 1.4, 1 to 1.25, 1 to 1.15, or 1 to 1.1. A fiber having a perfectly circular cross-sectional shape has a shape factor of 1. The shape factor can be calculated from the cross-sectional area and circumference of the fiber, both of which can be measured using a QIA.
[0081] Furthermore, in certain embodiments, one or more CTA fibers 52 may be in the form of solid fibers (fibers having a solid cross-sectional shape without the presence of pores therein) rather than hollow fibers.
[0082] As described above, the silk factor property helps determine the suitability of the CTA fibers produced by this method in downstream applications. Tenacity is a key property of a fiber that measures how much tension a fiber can withstand before breaking. Compared to breaking high-tenacity fibers, low-tenacity fibers can be broken with less force. For textile manufacturing, a tenacity below 1.5 g / den may be problematic because the fiber may break under normal operating conditions. In one embodiment or in combination with any other mentioned embodiments, the CTA fibers produced by this method may exhibit a tenacity of at least 1.5, or greater than 1.5, or at least 1.52, or at least 1.55, or at least 1.58, or at least 1.6, or at least 1.7, or at least 1.8, or at least 1.9, or at least 2.0, or at least 2.1, or at least 2.2, or at least 2.3, or at least 2.4, or at least 2.5 g / den, as measured according to ASTM D22556.
[0083] Elongation, also known as elongation at break, is expressed as a percentage and indicates how much a yarn or fiber will be able to stretch before breaking. In one embodiment or in combination with any of the other mentioned embodiments, the CTA fibers produced by this method can exhibit an elongation at break of at least 15%, or at least 16%, or at least 17%, or at least 18%, or at least 19%, or at least 20%, or at least 21%, or at least 22%, or at least 23%, or at least 24%, or at least 25%, or at least 26%, or at least 27%, or at least 28%, or at least 29%, or at least 30%, as measured according to ASTM D22556.
[0084] The Silk Factor (SF) is an empirically determined relationship between tenacity and elongation that is used to predict the failure envelope of a given fiber. The Silk Factor can be used to characterize the suitability of a yarn or fiber for a given process and is calculated based on the following formula:
[0085]
[0086] In one embodiment or in combination with any of the other mentioned embodiments, the CTA fibers produced by this method can exhibit a Silk Factor of at least 5.0, or at least 6.0, or at least 7.0, or at least 7.5, or at least 8.0, or at least 8.5, or at least 9.0, where the elongation is expressed as a percentage and the tenacity is expressed in grams per denier.
[0087] As mentioned above, the CTA fibers produced by this method are formed as continuous fibers. In one embodiment or in combination with any of the other mentioned embodiments, the fibers produced by this method can be continuous fibers or they can be cut to form staple fibers.
[0088] like Figure 1 As shown, one or more CTA fibers 52 may be wound onto a take-up roll 53, which provides tension and pulls the fibers out of the DCM-free coagulation bath 50, thereby directing the fibers to downstream steps of the process, which may include, for example, one or more additional coagulation steps, one or more washing steps, one or more post-spray draw stretching steps, one or more fiber finish application steps, one or more drying steps, one or more heat treatment steps, a crimping step, a cutting step, a winding step, a packaging step, or a combination thereof, which may be arranged in various orders.
[0089] Back to Figure 1 , the CTA fibers 52 formed in the first coagulation bath 50 may be gathered into a ribbon, bundle, or yarn 54. The ribbon, bundle, or yarn 54 may include a plurality of one or more CTA fibers 52. Each of these ribbons, bundles, and yarns may include at least 1, at least 10, at least 50, at least 100, at least 150, at least 200, at least 250, at least 300, at least 350, or at least 400, and / or no more than 10,000, no more than 5,000, no more than 1,000, no more than 900, no more than 800, no more than 700, or no more than 600 individual fibers.
[0090] After the wet spinning step, Figure 1As shown, the band, bundle or yarn 54 can be subjected to one or more post-jet draw stretching steps 60 so as to be subjected to post-jet draw stretching (PJDS). This PJDS differs from JDS in that the stretching occurs after the take-up roll 53 is driven (marking the end of the wet spinning step), so the fibers have already undergone some solidification and crystallization. Since the post-jet draw stretching of the fibers is performed after the material has partially solidified, it tends to cause more microscopic damage to the fibers if it is excessively performed. Therefore, post-jet draw stretching can increase toughness, but it also generally results in a significant reduction in elongation.
[0091] In the post-spray stretching step 60, the belt 54 may be subjected to additional stretching to further change the length and width of the yarn and change the polymer orientation within each fiber. The PJDS step may stretch the belt 54 in ambient temperature air, heated air, ambient temperature water, heated water, an aqueous solvent at ambient temperature, a heated aqueous solvent, steam, or any combination thereof. The post-spray stretching stretching step may include passing the belt 54 through a driven or speed-controlled stretching roller or stretching roller pair, which may apply heat to improve the ductility of the fiber. Increasing the temperature of the belt 54 may also be achieved by passing the belt 54 through a hot water bath or steam box or hot air stream to fully soften the fibers for stretching. Generally speaking, the speed (v) of each successive stretching roller or stretching roller pair is 20°C. out ) is greater than the speed of the previous stretching roller or stretching roller pair (v in ), so that the ribbon 54 is stretched, which can impart additional crystallinity and reduce the denier per filament when the ribbon 54 is fully stretched. The total post-jet stretch stretch ratio is calculated by multiplying the PJDS ratios of all one or more post-jet stretch extension steps included in the method. For example, if the method is configured with three post-jet stretch extension steps, the PJDS ratios applied thereto are 1.10, 1.25, and 1.33, respectively, then the total post-jet stretch stretch ratio will be (1.10 x 1.25 x 1.33) or 1.83. In one embodiment or in combination with any other mentioned embodiment, the post-jet stretch extension and post-jet stretch extension steps can be combined with a washing step, a fiber finish application step, a drying step, and / or a heat treatment step.
[0092] Before or after the post-spray stretching step 60, the ribbon 54 may be introduced into one or more additional coagulation baths 70 and / or one or more washing steps 80. These additional coagulation baths typically contain the same solvents and operating conditions as the first coagulation bath 50, but typically involve lower solvent levels than the first coagulation bath 50. Alternatively, additional coagulation baths may be eliminated in certain embodiments, or optionally replaced with one or more washing steps.
[0093] The washing step 80 may include directing the belt 54 through a bath containing water at various temperatures to facilitate removal of residual solvent from the belt 54. The washing step may also include spraying water onto the belt 54. Washing temperatures are generally between about room temperature and 99° C., but it has been observed that higher washing temperatures tend to alter the properties of the fibers produced by the process. Therefore, it may be desirable to use a washing temperature below 90° C., or below 75° C., or more desirably below 50° C.
[0094] In one embodiment or in combination with any of the other mentioned embodiments, after leaving the final washing step 80, the washed belt 54 may then be subjected to a fiber finish application step.
[0095] After any washing steps and finishing agent application steps, the belt 54 may be subjected to one or more drying steps 90. The one or more drying steps 90 may include any conventional drying equipment known in the art, including but not limited to hot air drying (unconstrained or partially constrained), infrared drying, heated godet drying, and air perforated drum drying. Generally, when the belt 54 is dried, the fibers that make up the belt will shrink or contract in the axial and longitudinal directions. In one or more drying steps, the belt 54 is not constrained to prevent all longitudinal contraction. The fibers of the belt 54 can be dried unconstrained and completely contracted in the longitudinal direction by allowing the belt 54 to be deposited on a moving dryer conveyor, wherein no tension is applied to the contracted fibers of the belt. Alternatively, the fibers of the belt 54 can be partially constrained to dry, wherein they partially contract or completely contract depending on the tension applied to the belt as it dries. By changing the exit velocity of the belt 54 when it leaves the drying step relative to the inlet velocity of the belt 54 when it enters the drying step, the amount of tension applied to the belt 54 when it dries can be controlled. If the inlet velocity and the exit velocity are equal, the belt 54 is considered fully constrained, wherein no longitudinal contraction occurs as the fibers of the belt 54 dry. When the exit velocity of the belt 54 is less than the inlet velocity, the belt 54 contracts as it dries. The belt 54 is fully contracted when the exit velocity of the belt 54 cannot be reduced and no slack forms as the belt 54 dries. Any exit velocity less than the inlet velocity but greater than the fully contracted velocity will result in partial contraction of the belt 54.
[0096] In one embodiment or in combination with any of the other mentioned embodiments, the belt 54 may be subjected to one or more heat treatment steps 100 before or after the one or more drying steps 90. The one or more heat treatment steps 100 may include any conventional annealing equipment, autoclave equipment, or a combination thereof known in the art. Typically, the heat treatment method steps include: (i) heating the fiber or belt to a temperature above half of its melting point, (ii) maintaining the fiber or belt at said temperature for a period of time, and (iii) subsequently cooling the fiber or belt in a manner that reduces the internal stress of the fiber. In one or more heat treatment steps, the belt 54 may not be constrained in a manner that prevents all longitudinal contraction. The fibers or belts may be heat treated unconstrained, where they are free to contract in the longitudinal direction by allowing the belt 54 to be deposited on a moving conveyor, where no tension is applied to the belt 54 during the heat treatment. Alternatively, the fibers of the belt 54 may be heat treated partially constrained, where they are allowed to contract partially or completely depending on the tension applied to the belt 54 during the heat treatment step. This tension may be controlled by varying the speed of the belt 54 at the entrance and exit of the heat treatment step, as in the drying step. One or more heat treatment steps 100 may be performed after or before the optional crimping step 110. In configurations where heat treatment is performed after crimping, it is believed that the heat treatment step helps to form the crimp pattern in the fiber. One or more heat treatment steps 100 may include heated air or steam and may be performed at atmospheric pressure, pressure above atmospheric pressure, or under vacuum. In some configurations, one of the heat treatment steps may be performed on finished packaging of the CTA fibers.
[0097] In another embodiment of the present invention, the heat treatment step 100 can be performed at a temperature at least 20 degrees below the Tg of the CTA fiber, at least 15 degrees below the Tg of the CTA fiber, and less than 10 degrees below the Tg of the CTA fiber.
[0098] In one embodiment or in combination with any of the other mentioned embodiments, the continuous fibers of the ribbon 54 may be accumulated onto bobbins, cores, or tubes in a packaging step 130. The packaging step 130 may include any conventional winding and packaging equipment known in the art.
[0099] In one embodiment or in combination with any of the other mentioned embodiments, the ribbon 54 can be subjected to a crimping step that at least partially crimps the CTA fibers. In one embodiment or in combination with any of the other mentioned embodiments, the CTA fibers and / or ribbon 54 can be crimped. Alternatively, in certain embodiments, the CTA fibers and / or ribbon 54 are not crimped.
[0100] The CTA fibers and / or ribbons 54 may be passed through a crimping zone, wherein a patterned wavy shape may be imparted to at least a portion or substantially all of the individual fibers. When used, the crimping zone includes at least one crimping device for mechanically crimping the CTA fibers. Generally, the CTA fibers are preferably not crimped by thermal or chemical means (e.g., hot water baths, steam, air jets, or chemical coatings), but rather are mechanically crimped using a suitable crimping machine. An example of a suitable type of mechanical crimping machine is a "stuffing box" or "stuffing box" crimping machine, which utilizes multiple rollers to generate friction, which causes the CTA fibers to bend and form crimps. Other types of crimping machines may also be suitable. Examples of suitable apparatus for imparting crimp to fibers are described, for example, in U.S. Patent Nos. 9,179,709; 2,346,258; 3,353,239; 3,571,870; 3,813,740; 4,004,330; 4,095,318; 5,025,538; 7,152,288; and 7,585,442, each of which is incorporated herein by reference to the extent not inconsistent with the present disclosure.
[0101] In one embodiment or in combination with any of the other mentioned embodiments, the crimping can be performed such that the CTA fiber has a crimp frequency of at least 5, at least 7, at least 10, at least 12, at least 13, at least 15, or at least 17, and / or no more than 30, no more than 27, no more than 25, no more than 23, no more than 20, or no more than 19 crimps / inch ("CPI") as measured according to ASTM D3937-12. In certain embodiments, the average CPI of the CTA fibers making up the belt 54 and / or various downstream products may be in the range of 7 to 30 CPI, 10 to 30 CPI, 10 to 27 CPI, 10 to 25 CPI, 10 to 23 CPI, 10 to 20 CPI, 12 to 30 CPI, 12 to 27 CPI, 12 to 25 CPI, 12 to 23 CPI, 12 to CPI, 15 to 30 CPI, 15 to 27 CPI, 15 to 23 CPI, 15 to 20 CPI, or 15 to 19 CPI.
[0102] In one embodiment or in combination with any of the other mentioned embodiments, when curled, the CTA fibers can have a curl amplitude that varies and can be, for example, at least 0.85, at least 0.90, at least 0.93, at least 0.96, at least 0.98, at least 1.00, or at least 1.04 mm. Additionally or alternatively, in one embodiment or in combination with any of the other mentioned embodiments, the CTA fibers can have a curl amplitude that is up to 1.75, up to 1.70, up to 1.65, up to 1.55, up to 1.35, up to 1.28, up to 1.24, up to 1.15, up to 1.10, up to 1.03, or up to 0.98 mm.
[0103] Additionally, in one embodiment or in combination with any of the other mentioned embodiments, the CTA fibers comprising ribbon 54 and / or the staple fibers produced therefrom can have a crimp ratio of at least 1:1. As used herein, "crimp ratio" refers to the ratio of the length of the non-crimped ribbon or fiber to the length of the crimped ribbon or fiber. In certain embodiments, the CTA fibers and / or the staple fibers produced therefrom can have a crimp ratio of at least 1:1, at least 1.1:1, at least 1.125:1, at least 1.15:1, or at least 1.2:1.
[0104] The curl amplitude and curl ratio were measured according to the procedures outlined in U.S. Patent Application Publication No. 2020 / 0299822, which is incorporated herein by reference to the extent not inconsistent with the present disclosure.
[0105] Additionally or alternatively, in one embodiment or in combination with any of the other mentioned embodiments, one or more types of surface finishes may be applied to the CTA fibers and / or the tape 54 formed therefrom. The application method is not limited and may include the use of spraying, wick application, dipping, or using a squeeze roller, lick roller, or kiss roller. The location where the finish is applied to the fibers or tape 54 may vary depending on the function of the finish. For example, a lubricating finish may be applied after spinning, before crimping, or before the fibers are gathered into a tape, bundle, or yarn. A cutting lubricant and / or an antistatic lubricant may be applied before or after crimping and before drying. Suitable amounts of all finishes on the CTA fibers, whether lubricants, cutting lubricants, antistatic finishes or otherwise, may be at least 0.01 wt%, at least 0.02 wt%, at least 0.05 wt%, at least 0.10 wt%, at least 0.15 wt%, at least 0.20 wt%, at least 0.25 wt%, at least 0.30 wt%, at least 0.35 wt%, at least 0.40 wt%, at least 0.45 wt%, at least 0.50 wt%, at least 0.55 wt%, or at least 0.60 wt% yarn finish ("FOY") relative to the weight of the dry CTA fibers. Additionally or alternatively, in one embodiment or in combination with any of the other mentioned embodiments, the cumulative amount of finish may be present in an amount of no more than 2.5 wt%, no more than 2.0 wt%, no more than 1.5 wt%, no more than 1.2 wt%, no more than 1.0 wt%, no more than 0.9 wt%, no more than 0.8 wt%, or no more than 0.7 wt% FOY, based on the total weight of the dry fibers. The amount of finish on the fiber (expressed as a weight percent) can be determined by solvent extraction. "FOY" or "yarn finish" as used herein refers to the amount of finish on the fiber or yarn minus any added water.
[0106] In one embodiment or in combination with any of the other mentioned embodiments, the CTA fibers can include at least one plasticizer, or in the alternative, no plasticizer. For example, the CTA fibers can be at least partially coated with a dry plasticizer. The CTA fibers can include less than 15 wt%, less than 12 wt%, less than 10 wt%, less than 9 wt%, less than 8 wt%, less than 7 wt%, less than 6 wt%, less than 5 wt%, less than 4 wt%, less than 3 wt%, less than 2 wt%, less than 1 wt%, less than 0.5 wt%, less than 0.1 wt%, less than 0.05 wt%, less than 0.01 wt%, less than 0.005 wt%, less than 0.001 wt%, or less than 0.0007 wt% of at least one plasticizer, based on the total weight of the CTA fibers. When present, the plasticizer may be incorporated into the CTA fiber itself by spinning a dope containing the plasticizer (contained in the sheet used to make the dope), and / or the plasticizer may be applied to the fiber surface by any method used to apply a finish. If desired, the plasticizer may be included in the finish formulation.
[0107] The resulting CTA fibers can be used to produce a variety of end products, such as towbands, staple fibers, filament yarns, spun yarns, woven articles, nonwovens, and / or knitted textiles.
[0108] In one embodiment or in combination with any of the other mentioned embodiments, the CTA fibers and / or tapes 54 described above can be cut into staple fibers in a cutting step 120. Any suitable type of cutting device can be used that is capable of cutting the fibers into the desired length without excessively damaging the fibers. Examples of cutting devices can include, but are not limited to, rotary cutters, paper cutters, extended break devices, reciprocating blades, or combinations thereof. Once cut, the CTA staple fibers can be baled or otherwise bagged or packaged for subsequent transport, storage, and / or use in a packaging step 130. In various embodiments, the staple fibers can have a d50 length of at least 5 mm, at least 10 mm, at least 20 mm, at least 30 mm, at least 40 mm, or at least 50 mm, and / or no more than 150 mm, no more than 140 mm, no more than 130 mm, no more than 125 mm, no more than 120 mm, no more than 115 mm, no more than 110 mm, no more than 105 mm, no more than 100 mm, or no more than 95 mm.
[0109] Additionally or alternatively, in one embodiment or in combination with any of the other mentioned embodiments, the denier per filament (weight in grams for 9000 m of fiber length) or "DPF" of the CTA fibers (whether CTA staple fibers or CTA continuous fibers) can be in the range of 0.5 to no more than 20, or 0.5 to no more than 15, or 0.5 to no more than 10, or 1 to no more than 8, or 1 to no more than 5, or 2 to no more than 4. The specific measurement method is not limited and includes the ASTM 1577-07 method using the FAVIMAT vibrometer procedure (if fibers from which cut staple fibers can be obtained), or microbalance weight measurement or width analysis of samples of known length using any convenient optical microscope or analyzer. The DPF can also be correlated to the maximum width of the fiber.
[0110] Additionally or alternatively, in one embodiment or in combination with any of the other mentioned embodiments, the CTA fibers and / or CTA staple fibers produced therefrom can have an average cross-sectional width of at least 1, at least 2, at least 3, at least 4, at least 5, at least 6, at least 7, at least 8, at least 9, at least 10, at least 11, at least 12, at least 13, at least 14, at least 15, at least 16, at least 17, at least 18, at least 19, or at least 20 microns, and / or no more than 300, no more than 200, no more than 150, no more than 100, no more than 90, no more than 80, no more than 70, no more than 60, no more than 50, no more than 40, no more than 30, or no more than 25 microns. In certain embodiments, individual cellulose ester fibers and / or staple fibers produced therefrom can include an average width in the range of 1 to 300, 2 to 200, 3 to 100, 4 to 70, 5 to 50, or 8 to 30 microns.
[0111] In one embodiment or in combination with any of the other mentioned embodiments, the staple fibers may be formed into CTA spun yarns. Spun yarns are continuous strands composed of staple fibers that are mechanically entangled by a staple yarn spinning process. The staple yarn spinning process may be, but is not limited to, ring spinning, open end spinning, air jet spinning, compact spinning, sirospinning, vortex spinning, worsted spinning, semi-worsted spinning, woolen spinning, and flax wet spinning.
[0112] In one embodiment or in combination with any of the other mentioned embodiments, the CTA fibers can be formed into nonwoven articles, such as nonwoven textiles. Exemplary nonwoven articles can include wet-laid nonwoven articles, air-laid nonwoven articles, carded articles, and / or dry-laid nonwoven articles.
[0113] In one embodiment or in combination with any of the other mentioned embodiments, the CTA yarn can be formed into a woven article, such as a woven textile. The woven textile can be formed by interweaving at least two yarns (warp and weft) on a loom, wherein the warp yarn strands are oriented in parallel, and the weft yarns are interwoven in an alternating pattern over and under the warp yarns at an angle to the warp yarn orientation.
[0114] In one embodiment or in combination with any of the other mentioned embodiments, the CTA yarn can be formed into a knitted article, such as a knitted textile. Such a knitted textile can be formed from interlocking yarn loops.
[0115] In one embodiment or in combination with any of the other mentioned embodiments, the end products described herein (including staple fibers, yarns, nonwovens, knitted articles, and woven articles) may contain at least 0.25 wt%, at least 0.5 wt%, at least 0.75 wt%, at least 1 wt%, at least 2 wt%, at least 3 wt%, at least 4 wt%, at least 5 wt%, at least 6 wt%, at least 7 wt%, at least 8 wt%, at least 9 wt%, at least 10 wt%, at least 12 wt%, based on the total weight of the article. %, at least 15 wt %, at least 18 wt %, at least 20 wt %, at least 25 wt %, at least 30 wt %, at least 35 wt %, at least 40 wt %, at least 45 wt %, at least 50 wt %, at least 55 wt %, at least 60 wt %, at least 65 wt %, at least 70 wt %, at least 75 wt %, at least 80 wt %, at least 85 wt %, at least 90 wt %, at least 95 wt %, at least 99 wt %, or at least 99.9 wt % of one or more CTA fibers. Additionally or alternatively, in one embodiment or in combination with any of the other mentioned embodiments, the end products described herein (including staple fibers, yarns, nonwoven articles, knitted articles, and woven articles) may contain no more than 99 wt%, no more than 95 wt%, no more than 90 wt%, no more than 85 wt%, no more than 80 wt%, no more than 75 wt%, no more than 70 wt%, no more than 65 wt%, no more than 60 wt%, no more than 55 wt%, no more than 50 wt%, no more than 45 wt%, no more than 40 wt%, no more than 35 wt%, no more than 30 wt%, no more than 25 wt%, no more than 20 wt%, no more than 15 wt%, no more than 10 wt%, no more than 9 wt%, no more than 8 wt%, no more than 7 wt%, no more than 6 wt%, or no more than 5 wt% of one or more CTA fibers, based on the total weight of the article. In certain embodiments, the end product may be formed entirely of CTA fibers, or comprise one or more CTA fibers in a range of 0.25 wt % to 50 wt %, 1 wt % to 99 wt %, 1 wt % to 50 wt %, 50 wt % to 99 wt %, 1 wt % to 20 wt %, or 0.25 wt % to 5 wt %, based on the total weight of the article.
[0116] definition
[0117] It should be understood that the following is not intended to be an exhaustive list of defined terms. Additional definitions may be provided in the foregoing description, such as, for example, where context accompanies the use of a defined term.
[0118] As used herein, the terms "a," "an," and "the" mean one or more.
[0119] As used herein, the term "and / or," when used in a list of two or more items, means that any one of the listed items may be used alone, or any combination of two or more of the listed items may be used. For example, if a composition is described as containing components A, B, and / or C, the composition may contain only A; only B; only C; a combination of A and B; a combination of A and C, a combination of B and C; or a combination of A, B, and C.
[0120] As used herein, the terms "comprising, comprises, comprise, contain, containing, and contains" are open transition words that are used to transition from the object recited before the term to one or more elements recited after the term, wherein the one or more elements listed after the transition word are not necessarily the only elements that make up the subject matter.
[0121] As used herein, the terms "having, has, and have" have the same open-ended meaning as "comprising, comprises, and comprise" provided above.
[0122] As used herein, the terms "including, include, and included" have the same open-ended meaning as "comprising, comprise, and comprise" provided above.
[0123] As used herein, the terms "containing," "contains," and "contained" have the same open-ended meaning as "comprising," "comprises," and "comprise" provided above.
[0124] Numerical range
[0125] This specification uses numerical ranges to quantify certain parameters related to the present invention. It should be understood that when numerical ranges are provided, these ranges should be interpreted as providing literal support for claim limitations that only recite the lower limit of the range and claim limitations that only recite the upper limit of the range. For example, a disclosed numerical range of 10 to 100 provides literal support for a claim that recites "greater than 10" (no upper limit) and a claim that recites "less than 100" (no lower limit).
[0126] The claims are not limited to the disclosed embodiments
[0127] The preferred forms of the present invention described above are intended to be used as illustrations only and should not be used in a limiting sense to interpret the scope of the present invention. Those skilled in the art may easily make modifications to the above exemplary embodiments without departing from the spirit of the present invention.
[0128] The inventors hereby declare that they intend to determine and assess the reasonable and fair scope of the present invention under the doctrine of equivalents as it relates to any device that does not materially depart from the literal scope of the present invention as set forth in the following claims.
[0129] Example
[0130] The following examples are intended to illustrate the present invention, to teach those of ordinary skill in the art to make and use the present invention, and are not intended to limit the scope of the present invention in any way. As described below, several tests were performed on samples produced via the methods described in the present invention and comparative method conditions.
[0131] Example 1
[0132] The spinning solution was prepared in a 500 ml three-necked flask using cellulose triacetate (CTA) (Eastman CTAVM 149) from Eastman Chemical Co., Kingsport TN. CTA was dissolved in dimethylacetamide (DMAc) at a concentration range of 18 to 24 wt % (based on the combined weight of CTA and DMAc) and maintained at 90° C. for two hours. The stirrer speed was 400 RPM for the first 1.5 hours and then slowed to 150 RPM for the next 0.5 hours. The resulting spinning solution was cooled to 60° C. and degassed for 3 hours.
[0133] The spinning solution is transferred from a three-necked flask to a 50ml stainless steel syringe with an attached spinning assembly, which comprises a multifilament spinneret and a layer of filter medium with a nominal pore size of 8 microns. The syringe and the spinning assembly equipment are connected to a high-pressure injection pump, which can accurately measure the spinning solution, so that the spinning solution flow rate is controlled to + / -1%. The spinneret surface comprises 19 circular holes, and the diameter of each hole is 0.045mm (45 microns). The spinneret is immersed in a coagulation bath containing a DMAc aqueous solution. The concentration of DMAc in the coagulation bath varies from 25 wt % to 65 wt % based on the weight of all liquids in the bath. When the spinning solution is wet-spun through the holes on the surface of the submerged spinneret, it is formed into a CTA fiber. The CTA fiber passes through the coagulation bath and is guided to the drive take-up roll by a non-driven guide roller. The jet stretching extension ratio is controlled by adjusting the surface speed of the drive take-up roll. If the surface velocity of the take-up roll is less than the calculated velocity of the spinning solution leaving the surface holes of the spinneret, the resulting jet-draw stretch ratio will be less than 1.0, while if the surface velocity of the take-up roll is greater than the calculated velocity of the spinning solution leaving the surface holes of the spinneret, the resulting jet-draw stretch ratio will be greater than 1.0. From the driven take-up roll, the fiber is fed to a winder which winds the fiber onto a bobbin. The post-jet-draw stretch ratio is calculated by dividing the surface velocity of the driven take-up roll by the surface velocity of the driven take-up roll. The post-jet-draw stretch ratio is performed in air at room temperature.
[0134] The fibers on the bobbins were washed by immersion in deionized water in an overflowing water bath at room temperature for 10 minutes. After washing, the fibers were cut from the bobbins. These resulting loose fibers were dried in a convection oven at 120°C for 15 minutes.
[0135] Denier was measured according to ASTM D1577-07 (2018), tenacity and elongation were measured according to ASTM D3822 / D3822M-14 (2020), and the mechanical properties of the fibers were evaluated on FAVIMAT (test conditions: 25 mm gauge length, 15 mm / min strain rate, 0.05 g / den pre-tension). The filamentation factor was calculated based on the elongation and tenacity results.
[0136] As can be seen from Table 1, the mechanical properties of Comparative Samples 1-10 produced a silk factor below 8.0, while Samples 11 and 12 produced according to the present invention produced a silk factor greater than 8.5. Operation of the wet spinning process in accordance with the limitations of the present claims allows for a DCM-free process to produce CTA fibers having a silk factor greater than 8.0.
[0137]
[0138] Example 2
[0139] CTA (Eastman CTA VM 149) from Eastman Chemical Co., Kingsport TN was dissolved in DMAc at a concentration of 20 wt% CTA (based on the combined weight of CTA and DMAc) and stirred at 100° C. until the spinning solution was clear and free of visible swollen particles. The resulting spinning solution was filtered through a 15 micron polyester nonwoven filter media.
[0140] The CTA fibers were wet spun by extruding the filtered spinning solution at 60° C. through a spinneret having 500 circular cross-section holes. Two spinnerets were used to wet-spin the CTA fibers, one having a hole diameter of 0.040 mm (40 microns) and the other having a hole diameter of 0.060 mm (60 microns). The spinnerets were immersed in a coagulation bath containing a coagulation solution of 60 wt % DMAc and 40 wt % water or 40 wt % DMAc and 60 wt % water based on the total weight of the solution, and the temperature was controlled at 25° C. After exiting the spinneret, the fiber passed through the coagulation bath and was guided by a non-driven guide roller to a driven take-up roller.
[0141] The extruded fibers were drawn through the coagulation bath by a driven take-up roll, the speed of which was varied to control the Jet Draw Stretch Ratio (JDSR) from 0.4 to 0.7 when using a 40 micron spinneret and from 0.7 to 1.1 when using a 60 micron spinneret. The Jet Draw Stretch Ratio was controlled by adjusting the surface speed of the take-up roll relative to the calculated speed of the spinning solution leaving the spinneret.
[0142] After driving the take-up roll, the fiber was immersed and passed through a 25° C. stretching bath containing a solution of 50 wt % DMAc / 50 wt % water or 30 wt % DMAc / 70 wt % water (based on the total weight of the bath). The post-jet draw stretch ratio (PJDSR) applied in the stretching bath was 1.0 or 1.16.
[0143] The fiber is then passed through a wash bath containing 100% water and two pairs of wash godet rolls to remove residual DMAc. After washing, the fiber is wound onto bobbins. After the washed fiber is wound onto bobbins, the fiber is cut from the bobbins and dried in a convection oven at 120°C without tension to allow the fiber to shrink freely.
[0144] Elongation and toughness were measured using a Favimat M in accordance with DIN 53816. (Test conditions: 20 mm gauge length, 10 mm / min strain rate, 0.5 cN / tex pretension)
[0145] It can be seen from Table 2 that filament factors of 8.0 and higher can be produced by the method of the present invention. In this example, a higher jet drawing extension ratio contributes to a higher filament factor. Figure 3 This shows that the optimal coagulation bath concentration varies with the spinneret hole diameter. The highest silk factors produced using 60 micron holes were all spun into a 60% DMAc coagulation bath, while 40% DMAc provided the highest silk factor when using 40 micron holes. In addition, all of these samples were produced by unconstrained drying, which allowed them to fully shrink during the drying step.
[0146]
[0147]
[0148] Example 3
[0149] Spinning solution was prepared using Eastman CTAVM 149 flakes (Eastman Chemical Co., Kingsport TN). CTA was dissolved in DMAc at a concentration of 18% by weight CTA. The resulting spinning solution was filtered through a BEKIPORST 15AL / 3 nonwoven filter having a pore size of 15 microns. The filtered spinning solution was fed to a spinneret at a temperature of 90°C, wherein the spinneret had 60 circular cross-sectional holes, each having a diameter of 0.063mm (63 microns). The spinneret was immersed in a coagulation bath containing a solution of 60% by weight DMAc and 40% by weight water. After coming out of the spinneret, the fiber passed through the coagulation bath and was guided to the driven take-up roll by a non-driven guide roller. The jet stretching extension ratio was controlled by adjusting the surface speed of the driven take-up roll (relative to the calculated speed of the spinning solution leaving the spinneret). Samples 0 to 3 were produced in a coagulation bath maintained at 25°C, while samples 4 to 6 were produced in a coagulation bath maintained at 10°C. From the driven take-up roll, the fiber is fed into a winder which winds the fiber onto a bobbin. The bobbin is washed with room temperature water for 10 minutes by immersion in an overflowing water bath. After washing, some fiber samples are cut from the bobbin for unconstrained drying, while other samples are left on the bobbin to dry. These free fiber samples (cut from the bobbin) and the samples on the bobbin are dried in air at 120°C for 15 minutes. Drying the fiber on the bobbin constrains the fiber and limits its ability to shrink and relax during drying. On the other hand, fibers dried in a loose or free state will shrink and relax during the drying process.
[0150] Denier was measured according to ASTM D1577-07 (2018), tenacity and elongation were measured according to ASTM D3822 / D3822M-14 (2020), and the mechanical properties of the fibers were evaluated on FAVIMAT (test conditions: 25 mm gauge length, 15 mm / min strain rate, 0.05 g / den pre-tension). The filamentation factor was calculated based on the elongation and tenacity results.
[0151] From Table 3 and Figure 2-5 It can be seen that the drying step of the present invention results in unexpected improvements in the tensile properties and silk factor of the CTA fibers produced. Drying the fibers in an unconstrained state allows the fibers to shrink and relax in the longitudinal direction, resulting in unexpectedly higher elongation and silk factor than fibers constrained during the drying process. The silk factor obtained for the samples dried in a free state is significantly higher.
[0152] Table 3. Constrained (on the tube) drying vs. unconstrained (off the tube) drying
[0153]
[0154] Example 4
[0155] The cellulose triacetate spinning dope was prepared by first heating the solvent to the mixing temperature (nominally 90°C) in a glass jar. CTA flakes were then added to the heated solvent in an amount that would achieve the target % solids concentration for each experimental condition. Mechanical stirring was applied for 3 hours. The lid of the glass mixing jar had a hole sized to accommodate the shaft of a stirring rod while minimizing solvent evaporation. After mixing, the spinning dope was stored in an oven at the mixing temperature for one hour to allow bubbles to dissipate. The spinning dope was then transferred to another oven and stored at 60°C until testing.
[0156] Monofilament fiber samples were produced using a benchtop wet spinning line. A syringe pump metered the CTA spinning solution into a syringe fitting with a needle of 60 microns or 110 microns in diameter, which was immersed in the coagulation bath. The monofilaments were guided through and out of the coagulation bath by a non-driven guide roller. The temperature, DMAc concentration, and jet-draw stretch ratio were varied. The coagulation bath temperature was varied from 11°C to 20°C, the DMAc concentration was varied from 45 wt% to 60 wt% (based on the weight of all liquid in the coagulation bath), and the jet-draw stretch ratio was varied from 0.7 to 5.7. The jet-draw stretch ratio was controlled by varying the surface speed of the driving winding spool after the coagulation bath relative to the calculated speed of the spinning solution leaving the spinning needle. No post-jet stretch ratio was used. The fiber samples were wound onto a spool using a winder set to the same speed as the take-up roll.
[0157] After winding, the bobbins were washed for 5 minutes in a room temperature bath of either 100 wt% water or 70 wt% water and 30 wt% DMAc. The samples were dried at either 60°C or 110°C for 15 minutes, with some samples dried on the bobbin (constrained) and others cut from the bobbin before drying (unconstrained).
[0158] Denier was measured according to ASTM D1577-07 (2018), and tenacity and elongation were measured according to ASTM D3822 / D3822M-14 (2020). The mechanical properties of the fiber samples were evaluated on FAVIMAT (test conditions: 25 mm gauge length, 15 mm / min strain rate, 0.05 g / den pre-tension). The filament factor was calculated based on the elongation and tenacity results. The results are shown in Table 4.
[0159] like Figure 8 As shown, when the jet-drawing extension ratio exceeds 1 (more specifically, exceeds 1.4), the positive effect of unconstrained drying on the fiber's silk factor properties is less pronounced.
[0160]
[0161]
[0162]
[0163]
[0164] Example 5
[0165] Fiber samples were produced according to the method of Example 1 regarding spinning solution preparation, wet spinning and washing. The samples were then dried in a convection oven at 120°C for 10 minutes, some samples were cut from the bobbin before drying and were therefore allowed to shrink (unconstrained), while other samples were dried on a bobbin that was not allowed to shrink (constrained). The dried samples were cooled to ambient temperature and the fiber properties of selected samples were tested. The remaining samples, whether constrained or unconstrained dried, required an additional heat treatment step, even though they were in a convection oven at 180°C for 10 minutes. All samples were subjected to the heat treatment step in an unconstrained (off the bobbin) state.
[0166] Table 5 shows the effects of drying and annealing methods on the tensile properties and silk factor of CTA fibers of the present invention. Drying the fibers in an unconstrained state allows the fibers to relax and shrink, resulting in significantly higher elongation and only slightly lower toughness than fibers that were constrained by tube drying during drying. The resulting silk factor was also significantly higher for the samples dried in an unconstrained state. Secondary heat treatment of fiber samples dried in an unconstrained state resulted in slight changes in toughness, elongation, and silk factor. However, secondary heat treatment of fiber samples dried under constraint (on a tube) showed significant improvements in elongation and silk factor, while toughness remained almost unchanged. Unexpectedly, the elongation and silk factor properties of samples dried in a constrained state and subjected to an additional heat treatment step were almost restored to the levels exhibited by the fiber samples dried in an unconstrained state. Both unconstrained drying and unconstrained secondary heat treatment at appropriate temperatures and times can effectively relax the fibers, thereby obtaining higher silk factors.
[0167]
Claims
1. A method for producing one or more cellulose triacetate ("CTA") fibers having a silk factor greater than or equal to 8.0, the method comprising: a) a dissolving step in which triacetyl cellulose is dissolved in a dichloromethane-free solvent containing dimethylacetamide to produce a triacetyl cellulose spinning solution; b) a wet spinning step wherein the cellulose triacetate spinning dope is wet spun through a coagulation bath containing no methylene chloride maintained at a temperature of 20° C. to 40° C. at a jet draw extension ratio in the range of 0.3 to 1.4 to form one or more CTA fibers, wherein the bath comprises dimethylacetamide and water; and c) a drying step, wherein the one or more CTA fibers are dried and shrunk in the drying step.
2. The method of claim 1, wherein the one or more CTA fibers have a silk factor greater than or equal to 8.
5.
3. The method of claim 1 or 2, further comprising a heat treatment step, wherein the one or more fibers are heated to a temperature at least 10 degrees lower than the CTA fibers.
4. The method according to any one of claims 1 to 3, further comprising at least one post-jet draw stretching step, wherein the CTA fiber is further stretched to a total post-jet draw stretch ratio in the range of 1.0 to 3.
0.
5. The method according to any one of claims 1 to 4, wherein the concentration of dimethylacetamide in the coagulation bath free of dichloromethane is at least 20 wt% and not more than 65 wt%, based on the total weight of the coagulation bath.
6. The method according to any one of claims 1 to 5, wherein the concentration of water in the coagulation bath is at least 35 wt% and not more than 80 wt%, based on the total weight of the coagulation bath.
7. The method of any one of claims 1 to 6, wherein the one or more CTA fibers are partially or completely shrunk during the drying step.
8. The method according to any one of claims 3 to 7, wherein the heat treatment step further comprises steam and is carried out at a pressure greater than 1 atm.
9. The method according to any one of claims 1 to 8, further comprising a curling step.
10. The method of claim 9, wherein the curling step is followed by a heat treatment step.
11. The method of any one of claims 1 to 10, further comprising a cutting step, wherein the one or more CTA fibers are cut into CTA staple fibers.
12. The method according to any one of claims 1 to 11, further comprising a winding and packaging step of the continuous fibers.
13. The method according to any one of claims 1 to 12, wherein the degree of substitution of the acetyl substituents of the cellulose triacetate is greater than or equal to 2.
6.
14. The method of any one of claims 1 to 13, wherein the one or more CTA fibers have a denier per filament of 0.5 to no greater than 20.
15. The method according to any one of claims 1 to 14, wherein the cellulose triacetate spinning solution comprises a matting agent.
16. The method according to any one of claims 1 to 14, wherein the temperature of the cellulose triacetate spinning solution is within a range of 20°C to not higher than 120°C for wet spinning.
17. The triacetyl cellulose spinning solution according to claim 16, wherein the DS of the triacetyl cellulose is 乙酰基 is at least 2.6, and the number average degree of polymerization is not more than 200.
18. The triacetyl cellulose spinning dope according to claim 17, wherein the triacetyl cellulose spinning dope exhibits a viscosity of not more than 1,000 poise when measured at 90°C.
19. A cellulose triacetate fiber produced according to the method of any one of claims 1 to 18.
20. The triacetyl cellulose fiber according to claim 19, wherein the DS of the triacetyl cellulose is 乙酰基 is at least 2.6, and the number average degree of polymerization is not more than 200.
Citation Information
Patent Citations
Method for preparing an electrochromic device
US20200299822A1
Method for production of cellulose acetate staple
US2346258A
Yarn texturizing method and apparatus
US3353239A
Process for the production of crimped tow for cigarette filters
US3571870A
Tow guide for stuffer box crimping
US3813740A